Analysis of The Effect of Sleep Quality and Nutritional Intake on Toddlers' Weight Growth After Appetite Massage Intervention - Yuriati Putri; Khoiriyah Etika (Althar Cendikia Education, 2026)
Toddler weight gain is influenced by multiple factors, particularly nutritional intake and sleep quality. Although appetite-stimulating massage may improve comfort and appetite, its effectiveness depends on adequate nutrition and sufficient sleep. This study aimed to analyze the influence of sleep quality and nutritional intake on toddler weight gain following an appetite-stimulating massage intervention. An observational analytic study with a prospective cohort design was conducted among 30 toddlers selected through total sampling. The intervention consisted of a 15–20-minute appetite-stimulating massage administered twice weekly for eight weeks. Sleep quality was assessed using the Children's Sleep Habits Questionnaire (CSHQ), nutritional intake was evaluated through two-day 24-hour dietary recalls analyzed with NutriSurvey based on the Recommended Dietary Allowance (RDA), and body weight was measured before and after the intervention. Multiple linear regression analysis showed that sleep quality and nutritional intake jointly had a significant effect on toddler weight gain (F = 22.134; p = 0.001). The model explained 59.5% of the variance in weight gain (Adjusted R² = 0.595). Nutritional intake was the strongest predictor (β = 0.485), followed by sleep quality (β = 0.372). These findings indicate that adequate nutritional intake and good sleep quality significantly enhance toddler weight gain following appetite-stimulating massage, with nutritional intake being the most influential factor.